Changes in Sexual Activity and Function After Pelvic Organ Prolapse Surgery: A Systematic Review. Issue 5 (November 2020) - Antosh, Danielle D.; Kim-Fine, Shunaha; Meriwether, Kate V.; Kanter, Gregg; Dieter, Alexis A.; Mamik, Mamta M.; Good, Meadow; Singh, Ruchira; Alas, Alexandriah; Foda, Mohamed A.; Balk, Ethan M.; Rahn, David D.; et al.
Abstract : OBJECTIVE: We aimed to systematically review the literature to describe sexual activity and function before and after prolapse surgery. DATA SOURCES: We searched MEDLINE, EMBASE, and ClinicalTrials.gov databases from inception to April 2018. METHODS OF STUDY SELECTION: Prospective, comparative studies of reconstructive pelvic organ prolapse (POP) surgeries that reported sexual function outcomes were included. Studies were extracted for population characteristics, sexual function outcomes, and methodologic quality. Data collected included baseline and postoperative sexual activity, dyspareunia, and validated sexual function questionnaire scores. Change in validated scores were used to categorize overall sexual function as improved, unchanged, or worsened after surgery. TABULATION, INTEGRATION, AND RESULTS: The search revealed 3, 124 abstracts and identified 74 articles representing 67 original studies. The overall quality of evidence was moderate to high. Studies reporting postoperative results found higher rates of sexual activity than studies reporting preoperative sexual activity in all POP surgeries except sacrospinous suspension, transvaginal mesh, and sacrocolpopexy. The prevalence of dyspareunia decreased after all prolapse surgery types. The risk of de novo dyspareunia ranged from 0% to 9% for all POP surgeries except posterior repair, which lacked sufficient data. Overall sexual function based on PISQ-12 (Pelvic Organ Prolapse/Incontinence Sexual Questionnaire-12) scores improved for mixed native tissue repairs, anterior repairs, uterosacral suspensions, sacrospinous suspensions, and sacrocolpopexy; scores were similar for posterior repairs, transvaginal mesh, and biologic grafts. Sexual function did not worsen after any POP surgeries. CONCLUSION: Sexual function improves or remains unchanged after all types of reconstructive POP surgeries and does not worsen for any surgery type. Prevalence of total dyspareunia was lower after all POP surgery types, and de novo dyspareunia was low ranging 0–9%. This information can help surgeons counsel patients preoperatively. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42019124308. Abstract : Validated sexual function scores improve or remain similar after all types of reconstructive prolapse repairs.